The grasping hand : 'Kelo v. City of New London' and the limits of eminent domain - Somin, Ilya (Chicago : The University of Chicago Press, 2017)
In 2005, the Supreme Court ruled that the city of New London, Connecticut, could condemn 15 residential properties in order to transfer them to a new private owner. Although the Fifth Amendment only permits the taking of private property for 'public use,' the Court ruled that the transfer of condemned land to private parties for 'economic development' is permitted by the Constitution even if the government cannot prove that the expected development will ever actually happen. The court's decision in Kelo v. City of New London empowered the grasping hand of the state at the expense of the invisible hand of the market. In this detailed study of one of the most controversial Supreme Court cases in modern times, Ilya Somin argues that Kelo was a grave error.
"A Cato Institute book."
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 17, 2017).
Keywords: Eminent domain -- United States -- Cases; Zoning law -- United States -- Cases; Kelo, Susette -- Trials, litigation, etc; New London (Conn.) -- Trials, litigation, etc; Law; Connecticut; 21st century, c 2000 to c 2100.; Jurisprudence & general issues; Laws of specific jurisdictions & specific areas of law; Property law: general